Investigation of Cytotoxic Activity of Cyanobacterial Strains Isolated from Water and Soil Samples Collected in Hanoi - Trang, Ngo Thi; Anh, Tong Thi Ngoc; Khanh, Lai Ngoc; Hang, Tran Thi; Loan, Nguyen Thi Bich; Anh, Tran Thi Thuy; Lien, Nguyen Thuy; Lien, Nguyen Thi Thu; Hang, Pham Thi Luong (VNU Journal of Science: Natural Sciences and Technology, 2021)
As part of the ongoing efforts to exploit the pharmaceutical potential of domestic cyanobacteria, six strains belonging to the Nostocales order have been isolated from several sampling sites in Hanoi as prerequisite material. The cytotoxic activity evaluation based on the MTT test resulted in four extracts of two strains (HK7 and NK1111) exhibiting the inhibitory activity against HeLa cells, with IC 50 values ranging from 84.6 µg/mL to 257.3 µg/mL. The methanol extract of strain HK7 was further fractionated by LH-20 column chromatography to afford the K3 fraction, which inhibited 70% growth of HeLa cells at the concentration of 20.0 µg/mL. In addition, the high-resolution mass spectrometric analysis detected the presence of two natural compounds in the K3 fraction. Compound 1 showed the accurate mass of 352.2633 Da, suggesting a molecular formula of C 21 H 36 O 4 similar to two cytotoxic compounds 7Z-plakortide H or 10-gingerdiol. Compound 2 had the accurate mass of 278.1545 Da, suggesting a molecular formula of C 16 H 22 O 4 similar to four cytotoxic compounds pestaloficiol G, penicitrinol E-D, or isoversiol C.